ENHANCING THE ECONOMIC ROLE OF THE MOSQUE THROUGH EMPOWERMENT A Case Study in Yogyakarta City - Rizqi Anfanni Fahmi (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2018)
A large number of Muslim population in Indonesia is also suitable for a large number of mosques. Mosque in the history of Islamic civilization is a means to perform da’wah and development of economic resources of Muslims. Using descriptive qualitative methods, this study aims to examine how the economic role of the mosque can be improved through community empowerment program in Yogyakarta City, Indonesia. From the result, it may be concluded that mosque has a strategic position to empower congregation. For enhancing the economic role through empowerment, there are at least six steps. Firstly, planning process including agreement among the administrator, looking for fund source, and also looking for the partner. Secondly, socialization to the congregation, opened, closed, or limited. Thirdly, selecting the beneficiaries. Fourthly, the empowering process including lending a soft loan, establish cooperative, or marketing intervention. Fifthly, mentoring both economic and spiritual progress of the beneficiaries. The last process is evaluating the program periodically. The success indicators of this program are the performance of returning loans and the improving intensity of the congregation prayer.